The Environmental Toolkit for Teachers : First Steps to Sustainability. - Fraser, Neil (Bloomsbury Publishing, 2014)
The Environmental Toolkit for Teachers is the essential guide to reducing your school's ecological footprint and creating and embedding a sustainability ethos. Whether you are a teacher eager to make your classroom a more eco-friendly environment or a head teacher who wants to set up a whole school project, there are practical strategies and activities in this book for you. Written by an expert environmental education, this book includes 75 eco-projects and lessons that cover how to manage litter, waste and energy efficiently in a time saving, cost effective manner. Each project is tried and t.